Antioxidant activity, phenolics, polyphenols and flavonoids in the rhizomes and leaves of Zingiber officinale var. Rubrum - Muhammad, Abdullahi (2015)
Zingiber officinale var rubrum is a special cultivar of ginger that has distinctive genetic and phenotypic profiles. The use of synthetic antioxidants has been reported to have negative impacts on the consumers, this leads to tremendous increase in the interest for antioxidants from natural dietary sources especially for medicinal plants consumed as foods, beverages, condiments and spices like the ginger. Rhizomes and leaves of the ginger were exhaustively studied for their antioxidant activities (DPPH and FRAP), flavonoids, phenolics, polyphenols and primary metabolites contents. The effects of different growth stages and storage temperatures on the antioxidant activity and levels of phenolics, flavonoids and polyphenols were explored. Using the technique of HPLC, the flavonoid genistein was identified as one of the individual flavonoids in the plant. It was found that the rhizome extracts have the highest antioxidant activities of up to 57.55% DPPH and 20.27mg/g Trolox FRAP concentrations for the 70% methanol extracts. The flavonoid was found to be the most abundant compound among the three (phenolics, polyphenols and flavonoids) studied in the rhizomes whereas polyphenols were the most abundant in the leaves. The rhizomes have significant sugar content of up to 176μg/g Glucose FW and relatively lower protein content 48.50μg/gBSA FW. Storage temperature was found to significantly lead to the deterioration and degradation of phenolics, polyphenols, flavonoids and antioxidant activity. For example, FRAP and DPPH values of the control in the first week were 13.0mg/g Trolox DW and 58.82% respectively, these drastically fell to 7.23mg/g Trolox DW and 7.33% for the FRAP and DPPH respectively after storage at 700C for four weeks. Early vegetative stages of growth (8th week after germination) were found to be richer in flavonoids, phenolics, polyphenols, 18.74mg/g Quercetin DW, 4.70mg/g GA DW, and 16.6mg/gGADW respectively. The antioxidant was also higher than the later stages (12th and 16th weeks). The plant has enormous antioxidant content, genistein is identified to be a constituent flavonoid in the rhizomes of Z. officinale younger plants have higher antioxidant activity then older (for example, FRAP in the eighth and twelfth weeks were 16.70 and 14.45mg/gTrolox DW respectively while the DPPH percentage inhibitions were 56.80% and 50.05% for the eighth and twelfth weeks respectively) ones and also storage temperatures have so much effect on the total antioxidant.